The practice of experienced CEOs: Relational leaders challenging crisis situations - Soela, Vanderlei; Carvalho Neto, Antônio; Versiani, Fernanda; Diniz, Daniela Martins (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: Most studies on leadership mainly focus on the role of the leader, seeking to understand the most appropriate style of behavior to lead, considering leadership a one-sided phenomenon. As a result, they end up neglecting some important roles among those led, such as, for example, the reciprocal relationship between leaders and followers and the influence of organizations in this relationship. Moving from the understanding of a traditional leadership to a Relational Leadership becomes, therefore, an important step towards understanding the phenomenon of leadership. Purpose: This article analyzes how highly successful and experienced CEOs who have been leading large corporations perceive the influence of Relational Leadership to overcome moments of organizational and personal crisis. Method: In the qualitative research, semi-structured interviews were conducted with 12 CEOs (9 men and 3 women, around 60 years old) that have been leaders of several corporations in Brazil and abroad for more than 30 years. Results: The results show that the CEOs perceived the strong and positive influence of relational leadership to successfully face economic, political and personal crisis. The CEOs practices are related to the Relational Leadership Theory: 1) multilateral relationship; 2) human social construction; 3) relationships based on trust; 4) collective dimension; 5) communication to foster better decisions. These practices were also identified as antidotes to the solitude of power inherent to the CEOs` position. Conclusions: Successful CEOs who have walked a long road leading corporations perceive the strong and positive influence of Relational Leadership to face crisis. So, the study has theoretical implications when it points out Relational Leadership as effective in crisis situations, since the literature relates crisis with transformational leadership in most cases.